CIRFF 2015 - Soirée d'ouverture et plenière d'ouverture avec Natasha Kanapé Fontaine (2015)
7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) Plénière d’ouverture sous le thème Penser Créer Agir avec : - Natasha Kanapé Fontaine, poète et slameuse. Lundi 24 août, salle Marie-Gérin-Lajoie, UQAM.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiféminisme; antiracisme; approches et analyses; environnement; féminisme autochtone; histoire et politique; identités; identités culturelles; justice sociale; maternité; mohawk; poésie; périodes historiques; québec; ressource en ligne; régions géographiques; terre nouricière; territoire; thématiques; écriture des femmes*

"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Working women in transition to motherhood in Italy - Bertolini, Sonia; Musumeci, Rosy; Naldini, Manuela; Torrioni, Paola Maria (Journal of Romance Studies, 2015)
This article deals with the changing relationship between work and motherhood during the first pregnancy among a group of twenty-one highly educated women living in Turin (Northern Italy), who were interviewed during the months before childbirth with their male partners, in 2010-2012. It aims to illustrate the tensions between the dominant ideas and ideals of motherhood (the 'intensive mothering' model) and the pressing demands of the changing labour market. The data shows that ideas, plans and decisions concerning childcare arrangements are highly gendered, being influenced by the expectations of partners, employers and colleagues and by a work culture which is not family friendly. Within this Italian social and political context, a mother-to-be faces a dilemma which is perceived as a private issue that concerns only herself. The new transition to parenthood forces women to redefine their identity and career in a highly gendered manner. © Institute of Modern Languages Research 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; charge mentale; conciliation famille-travail; europe; famille; italie; maternité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Stability and transformation in gender, work, and family: Insights from the second shift for the next quarter century - Blair-Loy, Mary; Hochschild, Arlie; Pugh, Allison J.; Williams, Joan C.; Hartmann, Heidi (Community, Work and Family, 2015)
Arlie Hochschild's The second shift: Working families and the revolution at home argued that the revolution toward gender equality in the USA has been stalled due to three factors: (1) women continue to do most of the ‘second shift’ – the unpaid work of childcare and housework; (2) insufficient flexibility in the workplace for accommodating family caregiving needs; and (3) a deficit of public sector benefits, such as paid parental leave. Since the book's publication in1989, many aspects of the gender structure (how gendered opportunities, barriers, and cultural meanings are socially structured in the USA) remain the same. Yet many aspects have changed. This article looks at areas of stability in the gender structure and areas of transformation in the past quarter century. We then plumb the book for the analytical insights it generates for scholars today. We discuss how deep-seated cultural understandings of gender infuse all levels of analysis: macro-level policies, family and work institutions, and personal experiences of gender, intimacy, and moral commitments. These insights help illuminate paths forward for new research on how new economic developments, including economic insecurity, flexibilization (the increasingly reliance on temporary and contract labor), and the widening social class divide, continue to affect intimacy at home. © 2015 Taylor & Francis.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; discipline; double journée de travail; histoire et politique; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail domestique; états-unis